Aloe Emodin Alleviates Radiation‐Induced Heart Disease via Blocking P4HB Lactylation and Mitigating Kynurenine Metabolic Disruption - Fan Ouyang; Yaling Li; Haoming Wang; Xiangyang Liu; Xiaoli Tan; Genyuan Xie; Junfa Zeng; Gaofeng Zeng; Qiong Luo; Hong Zhou; Siming Chen; Kai Hou; et al. (Advanced Science)
Abstract Aloe emodin is an anthraquinone of traditional Chinese medicine monomer, which plays a protective action in cardiovascular diseases. However, the regulatory mechanisms of aloe emodin in the protection of radiation‐induced heart damage (RIHD) are unclear. As a novel post‐translational modification, lactylation is considered as a critical mediator in inflammatory cascade and cardiac injury. Here, using a cross of differential omics and 4D label‐free lactylation omics, protein disulfide‐isomerase (P4HB) is identified as a novel target for lactylation, and aloe emodin inhibits the binding of lactate to the K311 site of P4HB. Aloe emodin stabilizes kynurenine metabolism through inhibition of aspartate aminotransferase (GOT2) accumulation on damaged mitochondria. Mechanistically, aloe emodin inhibits phosphorylated glycogen synthase kinase 3B (p‐GSK3B) transcription in the nucleus to repress the interaction of prostaglandin G/H synthase 2 (PTGS2) with SH3 domain of SH3 domain‐containing GRB2‐like protein B1 (SH3GLB1), thereby disrupting the functions of mitochondrial complexes and reducing SH3GLB1‐mediated mitoROS accumulation, eventually suppressing calcium‐binding and coiled‐coil domain‐containing protein 2 (NDP52)‐induced mitophagy. This study unveils the regulatory role of aloe emodin in RIHD alleviation through PTGS2/SH3GLB1/NDP52 axis, indicates aloe emodin stabilizes GOT2‐mediated kynurenine metabolism through P4HB lactylation. Collectively, this study provides novel insights into the regulatory mechanisms underlying the protective role of aloe emodin in cardiac injury, and opens new avenues for therapeutic strategies of aloe emodin in preventing RIHD by regulating lactylation.